Penggunaan Kinesik Dalam Pidato (Alhadharah: Jurnal Ilmu Dakwah, 2012)
KinesicsÂ Â  - this is one factor that can be used to increase the attractiveness of speech - as long as its use is right - in accordance with what we express. Expression of limb movement must be the result of due care, preparation, and habits as well as deepening the content of the speech delivered by the desire to be heard, acknowledged and obeyed. Limb movements that do not correspond to what was said can actually make the audience amused and drab. As well as facial expressions or mimic in speech equally important to note. Facial expressions have the impression speech amplifier, but do not be too forced and contrived. If this happens it will make the viewer amused, and possibly be a laughingstock.